Prototype carbon fiber composite deformable mirror - Kendrew, S; Doel, P; Brooks, D; King, A; Dorn, C; Yates, C; Dwan, R; Richardson, I; Evans, G (2007)
Research into novel technologies for active and adaptive optics is essential to ensure the required performance for the demanding science goals set for next-generation astronomical observatories. Both in space and on the ground, the potential gain from ultralightweight and thermally stable deformable optics is high. Surface quality, form, and a high level of stability during operation are important criteria for such mirrors. In 2006 we reported our initial results of the design and manufacture of a prototype carbon fiber reinforced polymer (CFRP) deformable mirror, including a description of the mirror's assembly with a stiff backing structure and actuator array, and an extensive characterization of the system. Here we discuss results of dynamical testing and influence function measurements as well as details of the methodology. Influence function shapes showed reasonable agreement with the finite element analysis predictions, confirming the suitability of the finite element method as a design aid for precision optical systems. While problems remain with this technology, our results highlight some important issues and provide useful guidelines for further research. © 2007 Society of Photo-Optical Instrumentation Engineers.